MANAJEMEN PENDIDIKAN EKONOMI JNANA DHARMA MENYEIMBANGKAN KOMPETENSI KOGNITIF DAN MORAL SISWA - Ni Nyoman Parmithi; I Putu Eka Indrawan; Ni Luh Putu Yesy Anggreni (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2026)
Educational management in economics at the junior high school level plays a strategic role in shaping both learning quality and students’ character development. However, economics learning practices are still largely oriented toward cognitive achievement and have not systematically integrated moral values. This study aims to examine economics education management oriented toward Jnana Dharma in balancing students’ cognitive and moral competencies. The study employed a descriptive qualitative approach conducted at SMP Negeri 6 Denpasar, involving economics/IPS teachers, eighth grade students, and learning documents as research subjects. Data were collected through observation, in-depth interviews, documentation studies and supported by questionnaires. The results indicate that the application of Jnana Dharma oriented economics education management effectively integrates economic rationality with moral values in the learning process. Questionnaire findings show that economic honesty achieved the highest average score, followed by understanding of economic concepts and social responsibility. These results suggest that moral values are more effectively internalized when systematically managed through educational planning, implementation and evaluation. This study concludes that Jnana Dharma oriented economics education management is a relevant strategic framework for developing junior high school students who are not only cognitively competent but also morally responsible in economic decision making